Evaluating variation in use of definitive therapy and risk-adjusted prostate cancer mortality in England and the USA. Issue 2 (24th February 2015) - Sachdeva, Ashwin; van der Meulen, Jan H; Emberton, Mark; Cathcart, Paul J
Abstract : Objectives: Prostate cancer mortality (PCM) in the USA is among the lowest in the world, whereas PCM in England is among the highest in Europe. This paper aims to assess the association of variation in use of definitive therapy on risk-adjusted PCM in England as compared with the USA. Design: Observational study. Setting: Cancer registry data from England and the USA. Participants: Men diagnosed with non-metastatic prostate cancer (PCa) in England and the USA between 2004 and 2008. Outcome measures: Competing-risks survival analyses to estimate subhazard ratios (SHR) of PCM adjusted for age, ethnicity, year of diagnosis, Gleason score (GS) and clinical tumour (cT) stage. Results: 222 163 men were eligible for inclusion. Compared with American patients, English patients were more likely to present at an older age (70–79 years: England 44.2%, USA 29.3%, p<0.001), with higher tumour stage (cT3-T4: England 25.1%, USA 8.6%, p<0.001) and higher GS (GS 8–10: England 20.7%, USA 11.2%, p<0.001). They were also less likely to receive definitive therapy (England 38%, USA 77%, p<0.001). English patients were more likely to die of PCa (SHR=1.9, 95% CI 1.7 to 2.0, p<0.001). However, this difference was no longer statistically significant when also adjusted for use of definitive therapy (SHR=1.0, 95% CI 1.0 to 1.1, p=0.3). Conclusions: Risk-adjusted PCM is significantly higher in England compared with the USA. This difference may be explained by less frequent use of definitive therapy in England.